Biosignature of self-injury behaviors in adolescence: Role of β-endorphin in an acute inpatient unit - Wang, Ping; Li, Chao; del Sol-Calderón, Pablo; Mallol, Leticia; Hernández-Álvarez, Elena; Donoso-Navarro, Encarnación; Gil-Ligero, María; Rosado-Garcia, Silvia; Sánchez-Lòpez, Antonio José; Martín-Moratinos, Marina; Bella-Fernández, Marcos; Blasco-Fontecilla, Hilario (Frontiers in Psychiatry, 2022)
Self-injurious behavior (SIB) (either non-suicidal self-injury, NSSI; or suicide attempts, SA) is a common reason for adolescent psychiatric emergency hospitalizations. Altered basal serum β-endorphin (BE) levels have been reported in adults with a history of SIB, but information is lacking in adolescents. We analyzed the psychoclinical profile and serum BE level of 39 adolescents admitted to the acute unit at a hospital in Spain due to SIB. The Mean (SD) serum BE level was high (190.53 ± 74.83). Regarding time sequence, the onset age of NSSI and SA were related (p < 0.001). The older the onset age of NSSI, the shorter the transition between NSSI and the onset of SA behavior (p = 0.05), but this difference does not lead the variation of BE (p = 0.81). Patients diagnosed with depression had lower serum BE levels than adolescents with other diagnoses (p = 0.03). Although adolescents who seem to be addicted to SIB had higher levels of BE, this finding was not statistically significant. The relationship between serum BE levels and SIB in adolescents requires further investigation.